Competence and independence in the training of future teachers (Pedagogy of Higher and Secondary Education, 2013)
Kampov S. P. Competence and independence in the training of future teachers.The article reveals the essence of educational category based on comprehension, generalization and systematization of modern scientists’ views. The article points the attempt of the concept genesis in the psycho-pedagogical literature. The author stated that the competence is a system of personality traits. These traits provide an effective, efficient and creative usage of knowledge and skills that help to solve the problems independently in professional situations and interests of the educational institution.
Keywords: competence; professional independence; teacher; pedagogical education; skills; abilities